Spanish Dentists' Awareness, Knowledge, and Practice Regarding COVID-19: A Multiple Regression Analysis - Yolanda Martínez-Beneyto; Veronica Ausina-Márquez; Antonio J. Expósito-Delgado; Antonio J. Ortiz-Ruiz; Francisco J. Ibañez-Lopez; Juan C. Llodra-Calvo; Manuel Bravo (Elsevier, 2021)
Introduction: During the first months of the coronavirus disease 2019 (COVID-19) pandemic, Spain had the highest mortality rate and the second-highest infection rate in the world. Objective: To analyze the occupational situation of dentists, hygienists, and dental auxiliary staff during the peak of the pandemic, after the state of alarm was declared in Spain, and when the state of alarm was declared. In addition, a possible relationship between the geographical distribution of infected people and the availability of individual protection systems was investigated. Material and Methods: A cross-sectional questionnaire was answered by 6470 dentists and dental staff via WhatsApp and social media. Results: A total of 1 in 4 dental professionals ceased working completely. Of those that kept working, 25.28% of dentists and 19.61% of hygienist-auxiliary were equipped with filtering face piece (FFP) 2 masks (P < .05), and 61.8% complied with the official protection recommendations set by the General Council of Dentists of Spain. Nearly 59.4% of respondents had symptoms, but only 1.5% of dentists were tested, with 14% of dentists in isolation at the time of response. Overall, it is suggested that 10% of dental professionals may have been in direct contact with the coronavirus. Conclusions: Direct contact of Spanish dental health professionals with severe acute respiratory syndrome coronavirus disease 2 (SARS CoV-2) has been high during the most active phase of the pandemic. Dental professionals did not have personal protective equipment (PPE) necessary to care for patients, a situation that justified the reduction in scheduled dental care and only emergencies being treated. The Spanish geographical regions with the highest number of contagions had the least amount of individual protective resources (FFP2 and FFP3 masks).